Strategy of selecting the scales of risk, prognosis, and disease severity in patients with acute decompensated heart failure - A. G. Arutyunov (Российский кардиологический журнал, 2013)
The assessment of the current disease severity in patients with the syndrome of acute decompensation of chronic heart failure (acute decompensated heart failure, ADHF) and the prediction of the risk of adverse events or in-hospital death remains one of the most important problems of current clinical practice. The need to consider the current disease severity while selecting the therapeutic strategy justifies the search for the most convenient and user-friendly risk scales. Aim. To identify the optimal risk scale for the use in patients with ADHF syndrome. The paper focusses on the key risk scales which assess the severity, prognosis, and death risk in this clinical group. The emphasis is on the instruments which can be easily used in the routine clinical practice and which do not require additional examination. Material and methods. The data on ADHF patients came from the City Clinical Hospital No. 4 Register. This epidemiological study included both retrospective analysis of the patients hospitalised earlier and the analysis of the data from currently hospitalised ADHF patients. Over 12 months, 1034 patients were included in the study: 662 retrospective cases and 372 currently hospitalised patients (54% women and 46% men; age 58–80 years). The following risk scales were used: Russian “Shocks”,USclassification (“warm and dry”), Killip and Kimball (1967), Forrester and Stevenson (1977), Seattle HF Model, and EFFECT. Results. Among the analysed risk scales, the most accurate prognosis was observed for the EFFECT scale, particularly for the estimation of the 30 and 360-day risk of death. The predicted 30-day number of deaths was 153, compared to the observed number of 148 (p=0,01). For the 360-day risk, the respective numbers were 352 and 337 (p=0,01). Conclusion. Based on the results obtained, all examined scales can be classified into two types: Type I – for the assessment of the current disease severity (with the “warm and dry” classification as the most informative and use-friendly scale); and Type II – for the prediction of life expectancy and death risk at Day 30 and Day 360 (with EFFECT scale as the best-performing instrument).